Estimation of Parameters for Surface Mounted Permanent Magnet Synchronous Motors - Kurum, Huseyin Yuce; Oksuztepe, Eyyup; Akin, Erhan (Ieee, 2019)
For field-oriented control, sensorless control, and direct torque control of the permanent magnet synchronous motor, the motor parameters must be known with great accuracy. In this method, when the motor starts for the first time, the resistance and inductance values of the motor are calculated with high accuracy. First, a low voltage is applied to the windings and the resistance value is calculated after the motor becomes stable. Then, the applied voltage is cut off, and the time constant of the motor is obtained. The motor inductance value is calculated from this time constant. The proposed method is simple, does not require much mathematical processing, and is very suitable for use in practice. For the validity of the method, Matlab/Simulink is confirmed in the simulation.
4th International Conference on Power Electronics and their Applications (ICPEA) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: Parameter estimation; Permanent magnet synchronous motor control; direct torque control